Peningkatan Hasil Belajar IPA melalui Model Pembelajaran Quantum Teaching pada Peserta Didik Kelas V SD Negeri Gedongtengen Yogyakarta: Bahasa Indonesia - Sheren Viona; Retno Utaminingsih; Ana Fitrotun Nisa (TRIHAYU: Jurnal Pendidikan Ke-SD-an, 2023)
This study aims to improve science learning outcomes through the Quantum Teaching learning model for fifth-grade students at SD Negeri Gedongtengen, Yogyakarta.  This research subject were class fifth grade totaling 26 students. This research is Classroom Action Research with the research model from Kemmis and Taggart, the process of implementing class action includes: the planning, implementation, observation, and reflection stages. The data collection technique used documentation techniques, observation techniques, and test techniques. The instruments used are test questions and observation sheets. The validity of the items was tested with SPSS 25 software, product moment correlation in cycle I obtained 23 valid questions, 7 items failed and while in cycle II, 24 items were valid, 6 items failed. Instrument reliability with SPSS 25 KR-20 software, cycle I item items obtained a reliability coefficient value of 0.876, and cycle II item items obtained a reliability coefficient value of 0.942. The results show that the Quantum model of teaching can improve science learning outcome TANDUR implemented with this steps; growing through by giving apperception, doing through direct experience, labelling through doing some exercises, demonstrate through presenting, repeat frequently through question and answer, and celebrating by giving songs and reward. The results of pre-action research showed that students' learning outcomes in science were low. The average value of the new class reached 61.1, while the percentage of completeness was 15.4%. After learning using the Quantum Teaching model which varied various learning methods in cycle I, the class average score increased to 63.71, while the percentage of completeness increased to 50%. Likewise, after improving Quantum Teaching learning in cycle I, which was accompanied by encouragement from researchers and guidance in groups to actively ask questions, provide feedback, strengthen, and distribute groups evenly in cycle II actions, further improving the science learning outcomes of class VA students. The class average value increased to 83.49, while the percentage of completeness increased to 84.6%.